Protein dynamics and mechanisms controlling the rotational behaviour of the bacterial flagellar motor. - Brown, M; Delalez, N; Armitage, J (2011)
The proteins that make up the bacterial flagellar rotary motor have recently been shown to be more dynamic than previously thought, with some key proteins exchanging with pools of proteins in the membrane/cytoplasm. It has also become clear that in addition to simply switching in response to chemosensory signals, the rotation of the bacterial flagellar motor can be slowed or stopped, using a clutch or a brake, by signals from metabolism and growth state.